Magnetoresonance properties of manganite-perovskite nanocomposite with Bi2223-superconductor additives at T = 300 K, 4.2 K - Kalmykova, T.V.; Polevoy, S.Yu.; Nedukh, S.V.; Tarapov, S.I.; Tarenkov, V.Yu. (Functional Materials, 2014)
Results of research of electron magnetic resonance absorption in nanocomposites with different ratios of La₀.₆Sr₀.₄MnO₃ manganite and superconductor Bi₁.₇Pb₀.₃Ca₂Sr₂Cu₃O₇₋x (Bi2223) additives in the wide range of frequencies of 22-40 GHz, 68-80 GHz are presented at temperatures T = 340 K and 4.2 K. The manifestation of two peaks in the Electronic Magnetic Resonance spectrum is assigned to appearance of collinear ferromagnetic and paramagnetic phases in the structure under study.